Penerapan metode AHP sebagai sistem pendukung keputusan pemilihan tempat kerja - Nugroho, Ade Oktafiawan; Veronica, Rahayu Budhiati (Unnes Journal of Mathematics, 2021)
This study aims to create a decision support method that is useful for undergraduate graduates to choose a workplace that suits their interests and abilities as well as to produce a computer program for a decision support system to choose a workplace that suits what the graduates want the scholar.The method used is a literature study, which is carried out by reading and analyzing books and journals related to decision support systems to choose a workplace using the Analytical Hierarchy Process (AHP) method. The purpose of this literature study method is to obtain references, making it easier to carry out this research. After the literature study method, the writer will collect the respondent’s data which will be processed using the AHP method. The next stage is to analyze the problem with the AHP method. By using the AHP method and studying the steps of the AHP, in order to obtain the priority order of the most appropriate business entities to be selected, which are sorted according to the total value of the Global Priority Table from the largest to the total weight value equivalent And finally the authors produced a computer program to determine the workplace called the PHP-based Workplace Decision Support System (DSS).